(untitled) (Research, Society and Development, 2020)
A satisfactory sex life is an integral part of human health, important for self-determination, and interpersonal relationships. Among the factors that affect the quality of sexual life include Vaginismus, a sexual dysfunction, which affects de female pelvic floor, inserted in the International Classification of Diseases (ICD-10), which is characterized by involuntary contraction of the muscles around the orifice of the vagina, causing pain and impossibility of penetration during the sexual act. The cause of Vaginismus is broad and multifactorial, considered to be the result of the combination of physical, emotional and psychological problems, applied to castrating, punitive, religious, and traumatic sexual experiences of women. It also triggered an anxiety syndrome as one of the factors with potential for negative interference with healthy sexual activity and a strong relationship with episiotomy. In view of the negative repercussion of this dysfunction, this article aims to compile these causes and highlight the treatment of vaginismus through a literature review. In addition to fostering professionals’ attention on the subject, since, despite the apparent climate of sexual freedom, consulting to talk about sexual difficulties is still It is a taboo, both as a result of patient’s inhibition, within the office with poor investigations of syndromes and disease from more intimate anamneses by experts. Keywords: Vaginismus; Womens´s Health; Sexual Behavior.